"Chemo-Knights" and "Radio-Robby": Provision of Information in Pediatric Oncology. Issue 2 (March 2016) - Ruhe, Katharina M.; Elger, Bernice S.; Wangmo, Tenzin
Abstract : Background: Information provision is an important step in enabling pediatric patients to participate in healthcare. Storybooks and patient information brochures represent a channel through which children and adolescents with cancer are informed about their illness. However, the use of such written materials has received little academic attention. Objective: The aim of this article was to carry out an exploratory analysis of written information resources for pediatric cancer patients. The potential of these to enhance patient participation will be discussed. Methods: A convenience sample of 16 written resource materials in English and German were chosen for analysis. Thematic coding was carried out to identify major themes. Results: Subthemes were summarized into 3 main categories: information on diagnosis, treatment, and illness experience. Information was provided on, for example, illness name and etiology, diagnostic and treatment procedures, emotions, and coping strategies. Conclusions: Storybooks and other written resources on cancer contain a broad array of information and describe illness-related issues to a varying extent. They represent an excellent possibility to ease patient participation in healthcare by providing them with necessary information while also inviting further discussion. Implications for Practice: Nurses and other healthcare professionals can use written resource materials to engage in discussions with pediatric patients concerning their illness. Nurses should be aware of the information children and adolescents receive in these materials in order to be able to adequately answer questions that may arise or identify misunderstandings as well as lack of information.